Investigation of anti-allergic activity of piceatannol from Rhodomyrtus tomentosa fruits - Sang, Vo Thanh; Nhat Minh, Nguyen Hoang; Quang, Ngo Xuan; Hoai, Pham Ngoc; Long Giang, Bach; Minh, Le Van; Huu Hung, Nguyen; Hieu Hoa, Nguyen Luong; Dai Hung, Ngo (Vietnam Journal of Biotechnology, 2021)
Piceatannol is a naturally occurring polyphenolic stilbene found in various fruits and vegetables. It has been reported to possess various pharmaceutical properties and health benefit effects such as anticancer, antidiabetes, antioxidant, anti-inflammation, and anti-obesity activities. Recently, Rhodomyrtus tomentosa fruits have been determined to contain a large amout of piceatannol. In this study, piceatannol was extracted and isolated from R. tomentosa fruits collected from Phu Quoc district. Moreover, the anti-allergic activity of piceatannol was investigated using RBL-2H3 cells as an in vitro experimental model. Firstly, piceatannol was isolated from ethyl acetate extract of R. tomentosa fruit powder via using a column chromatography and high performance liquid chromatography eluted by several types of binary solvent systems with different polarity. Subsequently, the characterization of the isolated compound was identified by using the mass spectrometer and nuclear magnetic resonance methods. The degranulation of mast cellls was examined via measuring the release of β-hexsosaminidase in the culture supernatant. Moreover, observation of cell morphology was conducted under the inverted microscope as the RBL-2H3 cells treated with 40 µM of piceatannol. In addition, the cytotoxic effect of piceatannol at the concentration treatment of 40 µM was also tested via MTT ((3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay. As the result, piceatannol treatment significantly inhibited the mast cell degranulation via reducing the β-hexsosaminidase release to 44% at the concentration of 40 µM. Moreover, piceatannol exhibited the protective effect against calcium ionophore-induced morphological change of the RBL-2H3 cells. Notably, no significant cytotoxic effect at the concentration treatment up to 40 µM of piceatannol was observed on RBL-2H3 cells. Therefore, piceatannol from the R. tomentosa fruits could be suggested as a potential anti-allergic agent for future therapeutics.